Extreme Geomagnetic Disturbances (GMDs) Observed in Eastern Arctic Canada: Occurrence Characteristics and Solar Cycle Dependence - Engebretson, Mark J.; Yang, Lily; Steinmetz, Erik S.; Pilipenko, Vyacheslav A.; Moldwin, Mark B.; McCuen, Brett A.; Connors, Martin G.; Weygand, James M.; Waters, Colin L.; Nishimura, Yukitoshi; Lyons, Larry R.; Russell, Christopher T. (Wiley Periodicals, Inc., 2024)
Extreme (>20 nT/s) geomagnetic disturbances (GMDs, also denoted as MPEs—magnetic perturbation events)—impulsive nighttime disturbances with time scale ∼5–10 min, have sufficient amplitude to cause bursts of geomagnetically induced currents (GICs) that can damage technical infrastructure. In this study, we present occurrence statistics for extreme GMD events from five stations in the MACCS and AUTUMNX magnetometer arrays in Arctic Canada at magnetic latitudes ranging from 65° to 75°. We report all large (≥6 nT/s) and extreme GMDs from these stations from 2011 through 2022 to analyze variations of GMD activity over a full solar cycle and compare them to those found in three earlier studies. GMD activity between 2011 and 2022 did not closely follow the sunspot cycle, but instead was lowest during its rising phase and maximum (2011–2014) and highest during the early declining phase (2015–2017). Most of these GMDs, especially the most extreme, were associated with high-speed solar wind streams (Vsw >600 km/s) and steady solar wind pressure. All extreme GMDs occurred within 80 min after substorm onsets, but few within 5 min. Multistation data often revealed a poleward progression of GMDs, consistent with a tailward retreat of the magnetotail reconnection region. These observations indicate that extreme GIC hazard conditions can occur for a variety of solar wind drivers and geomagnetic conditions, not only for fast-coronal mass ejection driven storms.Plain Language SummaryGeomagnetically induced currents (GICs) can give rise to the most extreme space weather impact of disrupting electric power distribution. GICs can be driven by extreme geomagnetic disturbances (GMDs) that are observed as large amplitude (several hundred nT amplitude) and rapid (5–10 min period) changes in the geomagnetic field. We found that extreme high-latitude GMDs occur throughout the solar cycle, but are preferentially observed during the declining phase of the solar cycle (the several year interval just past solar maximum) and in ...